SUDEP in the North American SUDEP Registry: The full spectrum of epilepsies. (16th July 2019) - Verducci, Chloe; Hussain, Fizza; Donner, Elizabeth; Moseley, Brian D.; Buchhalter, Jeffrey; Hesdorffer, Dale; Friedman, Daniel; Devinsky, Orrin
Abstract : Objective: To obtain medical records, family interviews, and death-related reports of sudden unexpected death in epilepsy (SUDEP) cases to better understand SUDEP. Methods: All cases referred to the North American SUDEP Registry (NASR) between October 2011 and June 2018 were reviewed; cause of death was determined by consensus review. Available medical records, death scene investigation reports, autopsy reports, and next-of-kin interviews were reviewed for all cases of SUDEP. Seizure type, EEG, MRI, and SUDEP classification were adjudicated by 2 epileptologists. Results: There were 237 definite and probable cases of SUDEP among 530 NASR participants. SUDEP decedents had a median age of 26 (range 1–70) years at death, and 38% were female. In 143 with sufficient information, 40% had generalized and 60% had focal epilepsy. SUDEP affected the full spectrum of epilepsies, from benign epilepsy with centrotemporal spikes (n = 3, 1%) to intractable epileptic encephalopathies (n = 27, 11%). Most (93%) SUDEPs were unwitnessed; 70% occurred during apparent sleep; and 69% of patients were prone. Only 37% of cases of SUDEP took their last dose of antiseizure medications (ASMs). Reported lifetime generalized tonic-clonic seizures (GTCS) were <10 in 33% and 0 in 4%. Conclusions: NASR participants commonly have clinical features that have been previously been associated with SUDEP risk such as young adult age, ASM nonadherence, and frequent GTCS. However, a sizeable minority of SUDEP occurred in patients thought to be treatment responsive or to have benign epilepsies. These results emphasize the importance of SUDEP education across the spectrum of epilepsy severities. We aim to make NASR data and biospecimens available for researchers to advance SUDEP understanding and prevention.